(untitled) (Web of Teachers: Inderscience Research, 2025)
This paper explores the concept of formative assessment as a crucial pedagogical tool aimed at improving the learning process and enhancing student success. It defines formative assessment as a continuous feedback mechanism that informs both educators and learners about the students’ understanding and skills throughout the educational journey. The study examines various formative assessment strategies, such as quizzes, peer reviews, and reflective journals, highlighting their effectiveness in fostering a supportive learning environment. By analyzing case studies and empirical research, the paper illustrates how formative assessments can be integrated into curricula to promote active engagement, self-regulation, and personalized learning pathways. Ultimately, it argues that when implemented thoughtfully, formative assessment not only aids in identifying areas for improvement but also empowers students to take ownership of their learning, leading to greater academic achievement and motivation.